2018
DOI: 10.1007/s11120-018-0525-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of Rubisco activase negatively correlates with Rubisco content in transgenic rice

Abstract: The relationship between ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and Rubisco activase (Rca) levels was studied using transgenic rice overexpressing maize Rca (OX-mRca) and knockdown transgenic rice expressing antisense Rca (KD-Rca). The ratio of Rubisco to total soluble protein was lower in OX-mRca, whereas it was higher in KD-Rca than in WT, indicating that Rca expression was negatively correlated with Rubisco content. The expressions of other Calvin-Benson-Bassham cycle enzymes such as sedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Our results showed that although the levels of the Rubisco protein were decreased in RCA-HI plants, the mRNA levels of RBCS and of the Rubisco large subunit (RBCL) gene remained unchanged ( Figure S1). Similar results were obtained for the RCA-overexpressing rice plants reported by Fukayama et al [31,32]. These results suggest that Rubisco content is regulated post-transcriptionally.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results showed that although the levels of the Rubisco protein were decreased in RCA-HI plants, the mRNA levels of RBCS and of the Rubisco large subunit (RBCL) gene remained unchanged ( Figure S1). Similar results were obtained for the RCA-overexpressing rice plants reported by Fukayama et al [31,32]. These results suggest that Rubisco content is regulated post-transcriptionally.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, in the present study of RCA-transgenic plants, the amounts of transketolase and transketolase-N were not affected (Figures 2 and 3). Similarly, Fukayama et al [32] reported no changes in several Calvin-Benson cycle enzymes in RCA-transgenic rice plants. These results suggest that the changes in RCA content affected Rubisco levels selectively.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations